(3eSGFd egeI efbhdI ef cJGH CZdGWis - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3JHJOF ef MQa GdSjf s
(3BNQgG (B:s
(3hJfJgi HMQa GdjGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B372 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(123) s
Keywords: (3GddZIs